Light scattering by a spherical particle with a time-periodic refractive index - Stefanou, I; P.A. Pantazopoulos; N. Stefanou (Journal of the Optical Society of America B, 2021)
A rigorous time Floquet method for the calculation of scattering of electromagnetic waves by a homogeneous spherical object, characterized by a periodically varying-in-time isotropic permittivity, is presented. The method is applied to the study of Mie scattering by such a modulated dielectric particle. Our results are in excellent agreement with the quasistatic adiabatic approximation in the slow-modulation limit. At higher modulation frequencies, a remarkable spectral response, including resonant inelastic scattering and frequency conversion as well as energy transfer between the dynamic sphere and the electromagnetic field, is revealed and consistently explained.